2012
DOI: 10.6061/clinics/2012(12)03
|View full text |Cite
|
Sign up to set email alerts
|

The effects of one-half of a soccer match on the postural stability and functional capacity of the lower limbs in young soccer players

Abstract: OBJECTIVE:Most injuries occur during the final 15 minutes of each half of a soccer match, suggesting that physical exertion may influence changes in neuromuscular control and the body's ability to stabilize the joints of the lower extremities. The aim of this study was to analyze the effects of one-half of a soccer match on the functional capacity and stability of the lower limbs in young soccer players.METHODS:We analyzed 27 soccer players by evaluating the functional capacity of their lower limbs using the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 21 publications
(26 reference statements)
0
19
0
2
Order By: Relevance
“…Higher COP variability may indicate various regulatory mechanisms manifesting in the ability to maintain balance by triggering random movements. The test results of Yamada et al [62] indicated that, in football players, along with the increase in sports advancement, the instability in the AP plane increases. Other studies [63] indicate that speci c training contributes to a decrease in the variability of body excretions.…”
Section: Group Differences In Postural Balance Skillsmentioning
confidence: 99%
“…Higher COP variability may indicate various regulatory mechanisms manifesting in the ability to maintain balance by triggering random movements. The test results of Yamada et al [62] indicated that, in football players, along with the increase in sports advancement, the instability in the AP plane increases. Other studies [63] indicate that speci c training contributes to a decrease in the variability of body excretions.…”
Section: Group Differences In Postural Balance Skillsmentioning
confidence: 99%
“…In another study, in which balance measurements were made after a 25-min treadmill run, it took approximately 15 min for the athletes participating in the study to return their balance performance to its initial level [ 65 ]. In another study, where balance measurement was performed with the biodex balance system before and during a soccer match, it was determined that the dominant leg balance performance of the players was impaired while no change was observed in the support leg balance performance [ 66 ]. In contrast to this, soccer players’ support leg balance skills were found to be negatively affected following the fatigue protocol in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the measurement of landing kinetics and kinematics in a fatigued state has identified both male and female subjects significantly increased peak proximal tibial anterior shear forces, increased valgus moments, and decreased knee flexion angles (10). Combined, these fatigue-induced neuromuscular alterations lead to an overall reduction in dynamic stabilization on ground contact (25), thus placing the lower limb at increased risk of injury. Specifically, these high-risk landing kinematics increase the risk of injury to both the ACL (33,57) and MCL (27).…”
Section: Fatiguementioning
confidence: 97%